The Lower Nubian ›C-Group Culture‹: A Brief Synopsis and Critical Review of the Current State of Research - Schröder, Marie-Kristin (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
The so-called C-Group culture is a distinct archaeological culture attested in Lower Nubia from ca. 2300–1800 B.C.E. Known since the beginning of the 20ᵗʰ century from investigations in Lower Nubia in the frame of the first Archaeological Survey of Nubia, this culture has been the focus of comprehensive research for more than a century. Material culture attributed to the C-Group, in particular the characteristic decorated ceramics, funerary customs, and settlement patterns, were thoroughly published in the main monograph by Manfred Bietak (1968). However, the state of research has since evolved considerably, and thus a revision of the C-Group became imperative. The aim of this paper is to present the current state of the art of the archaeological record of this culture, most notably the striking shift of its chronological phases. The C-Group features a shorter period of time and is only attested until the advanced 12ᵗʰ Dynasty of pharaonic Egypt.